2016
DOI: 10.1161/circresaha.116.309492
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Lipid Mediators Maresin 1 and Resolvin D2 Prevent Atheroprogression in Mice

Abstract: Rationale: Atheroprogression is a consequence of nonresolved inflammation, and currently a comprehensive overview of the mechanisms preventing resolution is missing. However, in acute inflammation, resolution is known to be orchestrated by a switch from inflammatory to resolving lipid mediators. Therefore, we hypothesized that lesional lipid mediator imbalance favors atheroprogression. Objective: To understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
173
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(185 citation statements)
references
References 55 publications
11
173
0
1
Order By: Relevance
“…Defective inflammation resolution can be caused by an imbalance between specialized proresolving mediators (SPMs) and proinflammatory lipid mediators in both human and mouse lesions (20,21). Using liquid chromatography-tandem mass spectrometry to assay a wide range of SPMs and proinflammatory lipid mediators in aortic extracts, we found that the global content of SPMs, including resolvin D2, D5, and E3, was significantly increased in Mertk CR extracts (Supplemental Table 1 and Figure 3D).…”
Section: Resultsmentioning
confidence: 96%
“…Defective inflammation resolution can be caused by an imbalance between specialized proresolving mediators (SPMs) and proinflammatory lipid mediators in both human and mouse lesions (20,21). Using liquid chromatography-tandem mass spectrometry to assay a wide range of SPMs and proinflammatory lipid mediators in aortic extracts, we found that the global content of SPMs, including resolvin D2, D5, and E3, was significantly increased in Mertk CR extracts (Supplemental Table 1 and Figure 3D).…”
Section: Resultsmentioning
confidence: 96%
“…In this context, several key features of clinically dangerous advanced plaques are characteristic of impaired resolution, including defective efferocytosis, plaque necrosis, and DAMP-mediated inflammation; thinning of the fibrous cap; and oxidative stress. Moreover, the ratio of resolving:inflammatory lipid mediators is markedly lower in advanced murine and human plaques compared with earlier lesions (Fredman et al, 2016; Viola et al, 2016). The therapeutic potential of enhancing resolution in chronic diseases like atherosclerosis could be substantial in that SPMs, unlike anti-inflammatory drugs, suppress inflammation and promote tissue repair in a manner that is less likely to compromise host defense than drugs directly targeting the inflammatory response (Serhan et al, 2007; Tabas and Glass, 2013) (below).…”
Section: Resolution Of Inflammation Is Impaired In Atherosclerosis Anmentioning
confidence: 90%
“…Besides inducing macrophage egress, also the phenotype shift from proinflammatory (M1) to proresolving macrophages (M2) by resolving lipid mediators can limit atherosclerosis [61, 62]. Resolving lipid mediators, e.g., maresin 1 or resolvin D2, might be a useful tool to resolve atherosclerosis [61] by encouraging apoptosis or stimulating efferocytic cell clearance without affecting the normal immune response or taking the risk of causing systemic inflammation of atherosclerotic-experienced egressed cells.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Resolving lipid mediators, e.g., maresin 1 or resolvin D2, might be a useful tool to resolve atherosclerosis [61] by encouraging apoptosis or stimulating efferocytic cell clearance without affecting the normal immune response or taking the risk of causing systemic inflammation of atherosclerotic-experienced egressed cells.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%